2019
DOI: 10.1002/oca.2510
|View full text |Cite
|
Sign up to set email alerts
|

Modeling stochastic operation of reservoir under ambiguity with an emphasis on river management

Abstract: An optimization problem of controlling a dam installed in a river is analyzed based on a stochastic control formalism of a diffusion process under model ambiguity: a new mathematical approach to this issue. The diffusion process is a pathwise unique solution to a water balance equation considering the inflow, outflow, water loss in the reservoir, and direct rainfall. Finding the optimal reservoir operation policy reduces to solving a degenerate parabolic partial differential equation: a Hamilton-Jacobi-Bellman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 108 publications
(126 reference statements)
0
11
0
1
Order By: Relevance
“…Remark 6 We observed that convergence of solutions to ( 70)-( 72) depends on the initial guess, implying its sensitivity against the initial guess. At the current stage, we have neither unique solvability nor stability results on the continuous system ( 67)-(69) and discretized system (70)- (72). Therefore, we utilize the ODE-based method as a tool to validate the finite difference scheme because the latter is more computationally stable for our problem.…”
Section: Empirical Numerical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Remark 6 We observed that convergence of solutions to ( 70)-( 72) depends on the initial guess, implying its sensitivity against the initial guess. At the current stage, we have neither unique solvability nor stability results on the continuous system ( 67)-(69) and discretized system (70)- (72). Therefore, we utilize the ODE-based method as a tool to validate the finite difference scheme because the latter is more computationally stable for our problem.…”
Section: Empirical Numerical Approachmentioning
confidence: 99%
“…The HJBQVI (20) is computed with the two different numerical methods, which is the ODE-based method using (70) through (72) and a verified finite difference scheme having a formally first-order accuracy [44]. In addition, the statistical indices of the controlled state dynamics are calculated.…”
Section: Numerical Computationmentioning
confidence: 99%
“…The environmental and hydrological information of Hii River and Obara Dam constructed at mid‐stream of the river is documented in the literature 59,60 . From 2018, a local fishery cooperative and the local government are trying to suppress the algae bloom in the downstream of Obara Dam by wisely using sediment stored in a huge hydraulic structure placed further downstream where a large amount of sediment is collected at each flood (For its details, see Yoshioka et al 56 ).…”
Section: Applicationmentioning
confidence: 99%
“…A recursive formulation allows us to numerically handle the optimality equation. An uncertainty‐aversion (ambiguity‐aversion) problem 57 is also considered as an advanced problem, motivated by the fact that accurately identifying the environmental dynamics is often difficult 46,58,59 . Our methodology can handle cases both with and without model uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…1 Stochastic control is a branch of the optimal control specialized for problems with noise-driven dynamics. 2 Management problems not limited to but include those of energy and resources, 3,4 population, 5,6 environment, 7,8 finance and economics, 9,10 and planning 11,12 have been analyzed as stochastic control problems.…”
Section: Introductionmentioning
confidence: 99%